Learning Model of Speaking Arabic: Field Research Based on Constructivism Theory at Al Muhsinin Islamic Boarding School Kerinci - Abdul Muid; Sulhi Muhamad Daud Abdul Kadir; Noza Aflisia; Neldi Harianto (Alsuna: Journal of Arabic and English Language, 2020)
Purpose - This study aimed to analyze the learning model for speaking Arabic in the perspective of constructivism theory at Al Muhsinin Kerinci Islamic Boarding School and teachers’ effort in supporting the learning model used. Design/methodology/approach - The research method used by researchers in this study was field research is descriptive qualitative. Findings - The results showed that the learning model of Arabic speaking skills at Al Muhsinin Kerinci Islamic Boarding School studied contextual learning models consisting of daily communication activities using Arabic, quantum learning models related to independent learning activities and further learning, cooperative learning models including activities morning vocabulary learning and Arabic conversation and problem-based learning models in Arabic discussion. Originality/value – Learning Arabic speaking skills for non-native speakers in the Boarding School needs to be constructed with complications from a compilation of various learning models. Paper type – Research Paper